High-resolution, single-particle digital autoradiography of actinide sources using microcapillary array collimators and the iQID camera. (December 2020) - Miller, Brian W.; Bowen, James M.; Morrison, Erin C.
Abstract: Characterization of the homogeneity of thin actinide deposits prior to and after irradiation is important to ensure measurement of high-quality nuclear data in nuclear physics experiments. Autoradiography is frequently used to assess homogeneity, but geometric blur from source thickness, particle range, and source-detector gap can significantly degrade image resolution and introduce bias when estimating source uniformity and activity. We establish a method for minimizing geometric blur using a new autoradiography imaging technique with microcapillary array collimators and a new method to characterize the homogeneity of an imaged deposit. Also, we demonstrate that beta-/gamma-blind imaging is possible for alpha-particle autoradiography with ZnS:Ag scintillators and the ionizing-radiation quantum imaging detector (iQID), a digital autoradiography system with intrinsic spatial resolutions up to 20 μm for alphas. This iQID imaging approach can successfully discriminate alphas in the presence of a beta-gamma source in samples containing >10 6 dynamic range in activity. We apply this feature to characterize the uniformity of plutonium deposits before and after accelerator irradiation in the presence of a large beta-gamma background. Highlights: We have developed a new and novel autoradiographic imaging technique with alpha particle emitters using microcapillary array collimators and the ionizing-radiation quantum imaging detector (iQID). We present a new method to characterize the homogeneity of an imaged alpha-emitting source deposit. We demonstrate beta-/gamma-blind autoradiography with alpha emitters using ZnS:Ag scintillators and the single-particle detection capability of the iQID